An Egg Parasitoid Efficiently Exploits Cues From a Coevolved Host But Not Those From a Novel Host - Bertoldi, Valeria; Rondoni, Gabriele; Brodeur, Jacques; Conti, Eric (Frontiers in Physiology, 2019)
Egg parasitoids have evolved adaptations to exploit host-associated cues, especially oviposition-induced plant volatiles and odors of gravid females, when foraging for hosts. The entire host selection process is critical for successful parasitism and relevant in defining host specificity of parasitoids. We hypothesized that naïve egg parasitoid females reared on their coevolved host are able to exploit cues related to the coevolved host but not those from a novel host. We used the egg parasitoid Trissolcus japonicus, its coevolved host Halyomorpha halys, and the non-coevolved host Podisus maculiventris to evaluate this hypothesis. H. halys, a polyphagous pest native from Eastern Asia, has invaded North America and Europe, resulting in serious damage to crops. T. japonicus is the most effective egg parasitoid of H. halys in its native area and thus considered a major candidate for biological control. This parasitoid was detected in North America and Europe as a result of accidental introductions. Laboratory host range of T. japonicus includes P. maculiventris, an American predatory stink bug used as a biological control agent of several pests. Using T. japonicus reared on its natural host H. halys, we tested in a Y-tube olfactometer the responses of naïve parasitoid females to volatiles from tomato plants with a deposited egg mass and feeding punctures of either H. halys or P. maculiventris. Additionally, using two different olfactometer set-ups, we tested T. japonicus responses to volatiles emitted by eggs and mature males and females of H. halys or P. maculiventris. Tomato plants subjected to oviposition and feeding by H. halys were preferred by the wasp compared to clean plants, suggesting a possible activation of an indirect defense mechanism. Furthermore, T. japonicus females were attracted by cues from gravid females and mature males of H. halys but not from eggs. By contrast, naïve parasitoid females never responded to cues associated with P. maculiventris, although this non-target host is suitable for complete parasitoid development. Such lack of responses might reduce the probability of T. japonicus locating and parasitizing P. maculiventris under field conditions. Our experimental approach properly simulates the parasitoid host-location process and could be combined with the required host specificity tests for risk assessment in biological control programs.